2021
DOI: 10.1016/j.jaim.2020.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Perception of service quality, satisfaction, and behavioral intentions in Ayurveda healthcare

Abstract: Background Based on the previous literature it is confirmed that Performance-based service quality and patient satisfaction are major antecedents of behavioral intentions in the healthcare sector. Here, the study deals with the same variables under the framework of Ayurveda healthcare. Objectives The study is an attempt to understand the perceptional differences of healthcare consumers in Ayurveda, by analyzing the relationship between the service quality, satisfaction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
3
20
0
1
Order By: Relevance
“…Aliman and Mohamad (2016) studied the satisfaction of the patients in public hospitals in Malaysia, found that satisfaction among the local patients plays a substantial mediating role in the relationship between their perceived service quality of the hospital and their revisit intention. Similarly, a study by Suhail and Srinivasulu (2020) and Jandavath and Byram (2016) also found that patient satisfaction partially mediates the relationship between service quality and patients' behavioural intention in private hospitals in India. In Malaysia, there are about 43 private hospitals are offering genealogy and obstetrics services (Association of Private Hospital of Malaysia [APHM], 2015).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Aliman and Mohamad (2016) studied the satisfaction of the patients in public hospitals in Malaysia, found that satisfaction among the local patients plays a substantial mediating role in the relationship between their perceived service quality of the hospital and their revisit intention. Similarly, a study by Suhail and Srinivasulu (2020) and Jandavath and Byram (2016) also found that patient satisfaction partially mediates the relationship between service quality and patients' behavioural intention in private hospitals in India. In Malaysia, there are about 43 private hospitals are offering genealogy and obstetrics services (Association of Private Hospital of Malaysia [APHM], 2015).…”
Section: Introductionmentioning
confidence: 80%
“…Research studies in the health-care setting have provided some evidence that hospitals' service quality has a positive influence on patient satisfaction, which, in turn, leads to patients' intention to return to a particular service provider (Aliman and Mohamad, 2016;Suhail and Srinivasulu, 2020). Research has found that patient satisfaction has a positive impact on patient loyalty (Meesala and Paul, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study support the findings of Rasheed and Abadi (2014) and Hapsari et al (2016) , which indicate that there is a positive relationship between SERVQUAL and CPV. Other studies were also validated which indicate that SERVQUAL has an indirect effect on both CS and BI ( Hapsari et al, 2016 ; Ryu and Han, 2010 ; Uzir et al, 2020 ; Suhail and Srinivasulu, 2021 ). The process of service providers to deliver packages is the same before and during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 96%
“… Uzir et al (2021) CS3 I think the package carrier has everything I needed to receive/send parcels during the COVID-19 pandemic. Suhail and Srinivasulu, 2021 CS4 I plan to avail or utilize the package carrier during the COVID-19 pandemic. Uzir et al (2021) CS5 I have easy access to the package carrier I need during the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…In services, quality can be assessed by comparing the actual performance of the service with customer expectations. The quality of services, according to Suhail and Srinivasulu (2020), can be a criterion for assessing the performance of a provider organization. Companies are dependent on the customer, therefore understanding their needs and expectations will lead to increased satisfaction, equivalent to a solid future of the organization.…”
Section: Literature Reviewmentioning
confidence: 99%